PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION DALAM MENANGGULANGI MASALAH WOMEN TRAFFICKING DI INDIA (2008-2013) - Yori Elfitriani; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to find out the role of International Organization for Migration (IOM) against women trafficking in India. IOM started its operations in India in the year 2001 to provide emergency relief in Gujarat when it was hit by an earthquake. While implementing the project in Gujarat, IOM was planning to expand its operations in India, it decided to work on the counter trafficking issue which was one of its mandated service areas. IOM, in close collaboration with Ministry of Overseas Indian Affairs (MOIA) has undertaken a number of initiatives. This research applies International Organization Role theory. The research method is descriptive with library research technique which use to collect and elaborate the information and data from the text books, papers, journals, and internet. The result of this research shows that the role of IOM against women trafficking in India is not effective. Trend of incidents of women trafficking is showing a steady rising during 2008-2013. The main cause why women trafficking increasing in India is poverty. According to the latest Millennium Development Goals report by the U.N, one third of the world‟s 1.2 billion poorest people live in India. Social inequality, regional gender preference, imbalance and corruption are the other leading causes of women trafficking in India. The Indian legal framework with respect to trafficking is severely flawed. While there are a large collections of statutes, existing international and regional conventions, active institutions, and a defined legal process that is designed to ensure that TIP offenders be prosecuted and TIP victims be protected, the legal framework is plagued by several weakness. The biggest problem remains in the implementation of the laws. Where laws are implemented, the penalties are not enough to deter trafficking or give adequate punishment. Keywords: International Organization for Migration (IOM), Women Trafficking, India, Poverty, Social inequality, Gender Discrimination